Vic-Tricarbonyl Compounds: Synthesis of (±)-9-epi-Wailupemycin A - Seitz, Tobias; Harms, Klaus; Koert, Ulrich (Synthesis, 2014)
A synthesis of the 9-epimer of the marine natural product wailupemycin A is reported. The key reaction sequence consists of a diastereoselective enamine addition to a tricarbonyl monohydrate, the formation of an enol silyl acetal, and finally the stereocontrolled addition of the α-pyrone substructure.
Keywords: vicinal tricarbonyl compound; enamine; α-pyrone; natural products; stereoselective synthesis